Enhancing social and lifelong learning skills through the use of mobile technology as a motivational factor - Danilah Salleh,; Norhaiza Khairudin,; Faidzulaini Muhammad,; Rozainee Khairudin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Growing use of technology by students is having an impact on teaching and learning as stu-dents are increasingly seeking to use technologies to engage in a range of academic activities. The traditional way of teaching and learning have to change in order to enhance students’ social and lifelong learning skills. Communicating with mobile phone have become a daily routine by most students. They are motivated to almost anything that involves mobile tech-nology. That is why they are spending hours with their phones. Thus, this study is done to recognize how mobile technology can help enhancing the social and lifelong learning of stu-dents through a case done in Seminar in Management Accounting class with the use of social and lifelong learning rubric and action research methodology. The study found that students have the opportunity to engage with the business communities through the use of mobile technology. The technologies enable them to engage with other party regardless of time and situations.